Ethnobotanical and ecological study of medicinal plants of mangroves in Siak District, Riau Province, Indonesia - Salmiah Safitri; Aras Mulyadi; Nofrizal Nofrizal; Dessy Yoswaty (SEHATI: Jurnal Kesehatan, 2024)
The mangrove forest in Kayu Ara Permai Village, Sungai Apit, Siak Regency, Riau Province, Indonesia, is a mangrove forest managed by the local community as the "Historic River" Mangrove Ecotourism Area. Mangrove forests have become a tourist attraction for many local and national tourists. The purpose of this study was to identify plants that have potential as medicinal plants in mangrove ecotourism areas of "Sungai Bersejarah" Kayu Ara Permai Village, Sungai Apit, Siak Regency, Riau Province. This study used a survey method in mangrove forests to conduct an inventory of the medicinal plants scattered throughout the area. Observations were made using a combination of the path and plot methods. The investigation was carried out by cross-checking the traditional use of medicinal plants by the surrounding community with the scientific literature. The results showed 7 species of medicinal plants from 5 different families, namely Avicennia alba, Rhizophora apiculate, Bruguiera parviflora, Bruguiera gymnorrhiza, Xylocarpus granatum, Sonneratia alba, and Acrostichum aureum. Mangrove density levels were in the sparse category (less than 1,000 trees/ha) and had low diversity levels, with two dominant species, Rhizophora apiculata and Xylocarpus granatum.